Medico-legal aspects of embolism with a case illustration - Sarvesvaran, R. (College of Pathologists, Academy of Medicine Malaysia, 1991)
An adult male sustained a number of stab injuries and other injuries including a fatal stab injury to the neck. There was evidence of air embolism which was considered to be a major factor causing death. The discussion is in four parts. Part I is confined to the post mortem examination. Part II relates to the medico-legal aspects of the case. Part III is a general discussion on embolism and its medico-legal significance whilst Part IV is on the medico-legal aspects of air embolism.